Actualization of information by euphemisms in legal texts - Булах, Майя Богданівна (Київський національний університет імені Тараса Шевченка, 2018)
The paper focuses on the analysis of the euphemistic process in Ukrainian legal discourse. It is generally known that the reader is already accustomed to actively using euphemisms in political speeches, speeches by politicians and officials, where they become a part of manipulative tactics. The use of euphemisms in such texts is also relevant, since the specifics of its communication are excessive courtesy, mitigation of statements, and excessiveness of etiquette formulas. Moreover, the specificity of public broadcasting requires figurativeness, which is reflected both in the mitigation of the expression and in the deliberate exaggeration, roughness, that called dysphemization. The article aims to explore the euphemistic mechanisms in Ukrainian legal texts. To solve this problem this paper presents different approaches to the definition of the phenomenon of euphemism. The materials for the study were chosen texts of annual reports of Kyiv city state administration for 2015-2017 years and Strategy of Kyiv development till 2025. This material allows us to investigate the functions of euphemistic means in the texts of official legal documents, which the main implicit function is the ideological impact on citizens. Focusing on positive achievements in the report, at the same time, it is necessary to reflect the existing actual state of affairs. Euphemisms allow speaker to do, as much as possible, soften the statement, conceal the negative effects of action. However, traditionally hidden things such as social inequality, poverty, illness, age restrictions etc. are veiled. It will be shown that this is obligatory and typical characteristic of political discourse. The author points out the motivation of creating euphemisms in the political discourse and communicative potential of euphemistic units. In particular, the following approaches are mentioned in the studies of the motivation of the creation of euphemisms: euphemism as part of the demobilization strategy and euphemism as a component of the method of emotional contamination, that is, the suggestive verbal technique used to create the mood desired by the audience. The author examines in detail various ways of euphemistic mechanisms due to its linguistic peculiarities, such as euphemisms as metaphorical nominations, euphemism-terms, euphemisms with a negative epithet, syntactic euphemistic substitutions, as well as a specific information delivery structure known as contrast-based manipulation and generalization.

Стаття присвячена дослідженню засобів евфемізації в юридичному дискурсі. Метою праці було висвітлити лінгвальні особливості евфемізмів в юридичних текстах. Матеріалом для вивчення були обрані тексти річних звітів Київської міської державної адміністрації 2015-2017 років та Стратегія розвитку м. Києва до 2025 року, розміщені на офіційному сайті КМДА. Теоретичним підґрунтям дослідження стали праці як українських, так і зарубіжних дослідників, що зосереджували свою увагу на особливостях уживання евфемістичних номінацій у суспільно-політичному, юридичному та медійному дискурсах. Основними питаннями аналізу стали функції евфемізмів та механізми і способи їх творення. Зокрема, серед функцій були виокремлені функція мітигації, пом’якшення, маскування, приховування заборонених або образливих висловів. Також було названо такі підходи в дослідженнях мотивації творення евфемізмів: евфемізм як складова частина стратегії демобілізації і евфемізм як складник методу емоційного зараження, тобто сугестивної вербальної техніки, яка використовується для створення необхідного настрою аудиторії. Окрім традиційних, визначено нову функцію евфемізмів у комунікації, як масовій, так і особистісній – вигідне самопрезентування мовця у процесі спілкування. Були висвітлені механізми творення евфемізмів, серед яких, зокрема, зазначено такі: процеси фонетичних змін, словотвірних модифікацій, використання запозичених слів та семантичних інновацій. Запропонований матеріал дозволив дослідити функції евфемістичних засобів у текстах офіційних юридичних документів, одна з імпліцитних функцій яких полягає у впливі. Евфемізми дозволяють відобразити існуючий фактичний стан речей, максимально пом’якшивши виклад, завуалювати негативні явища. Разом із тим, завуальовуються традиційно приховані речі, такі як соціальна нерівність, хвороби, вікові обмеження, що характерно для політичного дискурсу. У статті розглянуто різні способи евфемізації, такі як евфемізми з метафоричними номінаціями, евфемізми-терміни, евфемізми з епітетом негативного значення, синтаксичні евфемістичні заміни, а також специфічну структуру подачі інформації, відому як маніпуляція на основі контрасту та узагальнення.
Актуалізація інформації засобами евфемізації в юридичних текстах
Keywords: euphemism; functions of language; mitigation; manipulative influence; legal texts; евфемізм; функція; засоби мітигації; маніпулятивний вплив; юридичні тексти